A soja como estratégia de reprodução socioeconômica: o caso dos agricultores familiares de Guarani das Missões - RS - Marmilicz, Simoni Teresinha Jablonski (2013)
Soy is today an important symbol of Brazilian agribusiness and has taken its territory to deterritorialise significant part of household production at different scales . It is estimated that in Rio Grande do Sul the territorialization of soy had begun in 1900 in the municipalities of Pinheiro Machado and Dom Pedrito. In Guarani das Missões , soy , which is still intensely cultivated nowadays, was introduced in 1933 by the Polish agronomist Ceslau Mario Biezanko, its cultivation remained limited to small areas until mid 1960 . This research seeks to ascertain the impact of the modernization model introduced by soybeans , as well as their influences on the organization of rural and socioeconomic reproduction of family farmers from the municipality of Guarani das Missões - RS . Therefore, the research, that presents a qualitative approach , initially sought to make a brief history of territorial occupation and economic activities which are used for such in national , state and municipal scale. Afterwards, we proceeded to collect data on primary sources ( fieldwork ) and secondary sources, via agricultural census' data ( IBGE ) , the FEE and Emater . The fieldwork was carried out through interviews , directed to soybean's producers in the municipality and public agencies like the Municipal Agriculture's Secretary, Rural Workers's Union and EMATER from the municipality of Guarani das Missões - RS. Contrary to the preconceived notion that the soy was still the main crop of the municipality, in terms that it by itself or combined with other seasonal crops were ensuring socioeconomic reproduction of family farmers, we can say that its permanence and viability are result of other sources of income in rural areas , constituting nowadays as a possibility for crop rotation, as well as an extra income for the family farmers .